Short-term neonatal outcomes in vaginal breech delivery: Results of a retrospective single-centre study. (December 2022) - Fruscalzo, Arrigo; Londero, Ambrogio Pietro; Gerleve, Hubert; Riedel, Norbert; Jaspers, Karl-Dieter
Abstract: Background: Vaginal breech delivery (VBD) has been widely discouraged over the last two decades due to associated neonatal risks. However, many gynaecologists are still challenging this approach, at least in selected settings. Objective: To study short-term neonatal outcomes in singleton pregnancies undergoing VBD. Materials and methods: Retrospective cohort study conducted on singleton pregnancies who delivered in breech presentation between 2012 and 2019. Neonatal complications in terms of mortality, umbilical artery (UA) pH, 5-min Apgar score, and postnatal admission to neonatal intensive care unit (NICU) were evaluated. Results: Overall, 804 breech deliveries were considered. Of these, 53.86 % had VBD, 26.62 % had emergency caesarean sections (CS) and 19.53 % had elective CS. No perinatal deaths were reported. After multivariate adjustment, VBD was associated with higher incidence of UA pH < 7.10 compared with both elective and emergency CS. No significant associations were found between VBD and UA pH < 7.00 or 5-min Apgar score < 3 or < 7. No significant differences in NICU hospitalization were observed for different modes of delivery. Gestational age was inversely correlated with UA pH < 7.00, 5-min Apgar score < 3 and < 7, and NICU hospitalization. Conclusions: VBD in an experienced setting does not increase the risk of negative short-term perinatal outcomes significantly. Gestational age was the most important risk factor for low UA pH or 5-min Apgar score and NICU hospitalization, independent of mode of delivery.